[Cu]-catalyzed direct coupling of dibromoalkenes: Synthesis of symmetrical 1, 3-diynes and triazoles. Issue 12 (18th June 2017) - Mahendar, Lodi; Ramulu, Bokka Venkat; Satyanarayana, Gedu
ABSTRACT: An efficient [Cu]-catalyzed homocoupling of 1, 1-dibromoalk-1-enes is described for the synthesis of symmetrical 1, 3-diyines. The method showed good substrate scope and amenable to aryl and heteroaryl systems. Significantly, the strategy was also successfully applied to the sequential one-pot synthesis of triazoles. GRAPHICAL ABSTRACT: